Detection of infiltration from accidental causes with infrared thermography: case study - Aquino Rocha, Joaquin Humberto (2020)
Infiltration in buildings is one of the most frequent problems and, in most cases, is the product of pipe leaks, construction defects, among others. Their detection is difficult, since they do not present external manifestations in the first phases. Infrared thermography may be a potential technique for detecting these defects, since it does not need direct contact with the inspected structure and has real-time results. Thus, this article aims to evaluate infrared thermography to detect infiltrations due to accidental causes. The methodology of the work consisted in the inspection of the common areas of a multifamily condominium with a thermographic camera and the use of a humidity detector, in a complementary way. The results allowed to prove that the detection was possible with small thermal gradients, around 0.4 °C to 1.5 °C, where the affected areas were visualized with lower temperature due to the thermal inertia of the water. In the inspection for infiltration verification, the technique showed a rapid detection of this pathological manifestation and can be used as an auxiliary tool